1971
DOI: 10.1113/jphysiol.1971.sp009492
|View full text |Cite
|
Sign up to set email alerts
|

The influence of deep body temperatures and skin temperatures on peripheral blood flow in the pig

Abstract: SUMMARY1. The rate of blood flow through the tail of the pig has been measured by means of venous occlusion plethysmography using a mercury in rubber strain gauge. Conscious animals were used in all experiments because previous work had demonstrated that anaesthetics interfere with the animal's ability to vasoconstrict.2. Graded changes in the temperature of the hypothalamus were imposed by means of an implanted thermode. It was found that the change in blood flow depended on the extent of the change in hypoth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
36
0

Year Published

1973
1973
2006
2006

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(38 citation statements)
references
References 13 publications
2
36
0
Order By: Relevance
“…Moreover, the skin plays a key role in thermoregulation in pigs since it controls the rate of sensible heat transfer from the body core to the surface. Within the thermoneutral range of ambient temperature the loss of sensible heat from the body is mainly controlled by adjustment of tissue insulation in particular by change in peripheral blood flow [15]. In accordance with the results obtained in cattle [8], histological changes in the skin structure (number of epithelial strata, dermis thickness.…”
Section: Introductionsupporting
confidence: 72%
“…Moreover, the skin plays a key role in thermoregulation in pigs since it controls the rate of sensible heat transfer from the body core to the surface. Within the thermoneutral range of ambient temperature the loss of sensible heat from the body is mainly controlled by adjustment of tissue insulation in particular by change in peripheral blood flow [15]. In accordance with the results obtained in cattle [8], histological changes in the skin structure (number of epithelial strata, dermis thickness.…”
Section: Introductionsupporting
confidence: 72%
“…In the studies of Jessen and co-workers, heat production and evaporative heat loss responses elicited by cooling or warming of the spinal cord of the dog were very similar to responses elicited by comparable treatment of the hypothalamus and it was suggested that the cord and hypothalamus are basically equivalent core sensors of temperature (Jessen & Mayer, 1971;Jessen & Ludwig, 1971;Jessen & Simon, 1971). The temperature of the spinal cord in the pig is known to influence respiratory frequency (Ingram & Legge, 1972a), blood flow (Ingram & Legge, 1971) and oxygen consumption (Carlisle & Ingram, 1973), and to interact with thermal stimuli applied to the hypothalamus and scrotum (Ingram & Legge, 1972b).…”
Section: Introdiuctionmentioning
confidence: 99%
“…The thermodes were similar to those used in previous studies (Baldwin & Ingram, 1967;Ingram & Legge, 1971 hypothalamus consisted of two stainless-steel tubes ending in a disk-shaped tank 5 mm in diameter. The temperature of the spinal cord was sensed by a thermojunction inserted into a blind-ended polyethylene catheter positioned alongside the thermode.…”
Section: Thermode8 and Temperature Measurementmentioning
confidence: 99%
“…Amongst the thermosensitive regions in the body core, the preoptic region of the hypothalamus (Hammel 1968) and the spinal cord (Thauer, 1970;Klussmann & Pierau, 1972) are known to be of particular importance, although in some species (Rawson & Quick, 1970;Ingram & Legge, 1972) other regions are also involved. In the pig, heating or cooling the spinal cord produces changes in peripheral blood flow and evaporative heat loss (Ingram & Legge, 1971 of a similar nature to heating or cooling the hypothalamus, and on the basis of these results and studies on other species (Jessen & Mayer, 1971;Jessen & Ludwig, 1971;Jessen & Simon, 1971) it appears that thermal signals from the two regions are regarded by the control system as being more or less equivalent. Behavioural thermoregulation, as studied by the technique of operant conditioning can also be influenced by changes in the temperature of the hypothalamus in the pig (Baldwin & Ingram, 1967), but in a recent study, Carlisle & Ingram (1973) have demonstrated that heating or cooling of the spinal cord of the pig is accompanied by behavioural responses which differ from those observed when the hypothalamic temperature is changed.…”
mentioning
confidence: 96%
“…The temperature of the thermode was measured with the aid of a thermistor attached to the tank. The thermode over the spinal cord consisted of a loop of polyethylene 342 02 CONSUMPTION IN PIGS 343 tube inserted in the thoracic region at T10 and extending up to CI (Ingram & Legge, 1971;Carlisle & Ingram, 1973). The temperature of this thermode was assessed by threading a thermojunction down a blind-ended catheter inserted along with the thermode.…”
Section: Thermodesmentioning
confidence: 99%